Functional analysis of the internal translation initiation site of foot-and-mouth disease virus. - Kühn, R (1990)
Mutagenesis of the large untranslated sequence at the 5' end of the genome of foot-and-mouth disease virus revealed that a region of approximately 450 nucleotides preceding the open reading frame of the viral polyprotein is involved in the regulation of translation initiation at two internal start sites. Variations in two domains of this region reduced the translation efficiency up to 10-fold, whereas an intermediate segment seemed to be less essential. A pyrimidine-rich sequence preceding the start codon was most sensitive in that conversion of single pyrimidine residues to purines decreased the translation efficiency strongly. The data are in agreement with a recently proposed general structural model for the internal ribosome entry site of the cardiovirusaphthovirus subgroup of picornaviruses (E. V. Pilipenko, V. M. Blinov, B. K. Chernov, T. M. Dmitrieva, and V. I. Agol, Nucleic Acids Res. 17:5701-5711, 1989). They suggest, however, that this model represents only a core structure for the internal entry of ribosomes and that foot-and-mouth disease virus and other members of the picornaviruses need additional regulatory RNA elements for efficient translation initiation.